Monitoring of transport communications - Matsiy, М. E.; Aleksiyev, O. P.; Маций, Михайло Євгенійович; Алексієв, Олег Павлович; Маций, Михаил Евгениевич; Алексеев, Олег Павлович (Харківський національний автомобільно-дорожній університет, 2018)
Problem. Monitoring of transport communications is a new definition of a complex of works on the analysis of the status and reliability of individual units and the corresponding motor transport communication in general. The content of interactive monitoring is to monitor records continuously, accumulate and summarize data on the operational situation in the traffic environment. In connection with the constant information of society development and its industrial component, new transport systems and machines have reached a high level of information excellence. Accordingly, there is a new contradiction between the rapid development of means and methods of informatization of complex objects and systems and the heterogeneous nature of existing subsystems and units of the transport complex of Ukraine, which is also characteristic of the market of transport services. Methodology. The assessment and diagnosis of highways is based on their observation. A generalized means of such observation is their monitoring. It is he who provides not only monitoring of the condition of highways, but also the preparation of data for solving tasks of assigning tasks to road-operation services, road and transport enterprises and organizations. Results. The problem of solving this contradiction will allow to improve the service of the inhabitants of cities and regions at all levels of the transport infrastructure, to improve the transportation processes, to avoid the existing negative influences: crashes in the organization of traffic, poor state of communication, inappropriate use of funds allocated for repair, operation and arrangement of transport highways. The goal of monitoring (diagnostics and transport systems assessment) lies in obtaining full and adequate information about functional quality of transport communications, their work conditions and degree of actual consumer appeal conformity to vehicular traffic requirements. Practical value. The diagnostic results are basic for transport communications condition management and they are the original basis for efficient usage of means aimed at road network improvement and development.
Моніторинг транспортних комунікацій
Мониторинг транспортных коммуникаций
Keywords: computer systems; interactive monitoring; navigation; transport communication; комп’ютерні системи; інтерактивний моніторинг; навігація; транспортна комунікація; компьютерные системы; интерактивный мониторинг; навигация; транспортная коммуникация; 656:004.75; 10.30977/VEIT.2018.14.0.44